2020
DOI: 10.3390/ma13102395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filler Type on the Thermo-Mechanical Properties of Metakaolinite-Based Geopolymer Composites

Abstract: Metakaolinite-based geopolymer binder was prepared at room temperature by mixing calcined claystone and potassium alkaline activator. Various granular inorganic fillers were added, amounting to 65 vol % to form geopolymer composites. The effect of four types of fillers (sand quartz, chamotte, cordierite, and corundum) on the thermo-mechanical properties of metakaolinite-based geopolymer composites were investigated. The samples were also examined by an X-ray diffraction method to determine their phase composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…The decomposition of kyanite particles into mullite and cristobalite started at 1200 °C [ 17 , 21 ]. The nucleation of cordierite crystals from mullite, enstatite and cristobalite was observed with the presence of an endothermic peak at around 1280 °C [ 6 , 8 , 16 ]. This justified the stability of the refractory matrices ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decomposition of kyanite particles into mullite and cristobalite started at 1200 °C [ 17 , 21 ]. The nucleation of cordierite crystals from mullite, enstatite and cristobalite was observed with the presence of an endothermic peak at around 1280 °C [ 6 , 8 , 16 ]. This justified the stability of the refractory matrices ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
“…[ 5 , 7 , 12 , 13 , 14 , 15 ]. Among others, Kohout and Koutnik [ 16 ] investigated the effect of four filler types (quartz sand, chamotte, cordierite and corundum) on the thermo-mechanical properties of metakaolin-based geopolymer composites. They revealed that the addition of fillers reduced the thermal shrinkage of the geopolymer products and positively affected the development of mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the best performance in terms of lower porosity and higher strength was observed when 20% quartz or chamotte was used in the mixture. In a similar study, calcined kaolinitic claystone and potassium silicate hardeners were used to produce geopolymer samples [ 21 ]. Quartz, corundum, chamotte, and cordierite were used as fillers.…”
Section: Introductionmentioning
confidence: 99%
“…The geopolymer samples had a stable structure at an elevated temperature of 1000 °C, and the shrinkage of the geopolymer samples significantly reduced at high temperatures when the filler was used. The best fillers were corundum or chamotte, which performed better compared to the other types of fillers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cementing or geopolymerization process of geopolymer precursors with alkaline activators can rapidly proceed to form a three-dimensional polymeric structure with complex Al-O-Si bonds and to generate continual material skeletons that enable high strengths [10]. With those advantages, geopolymer-based materials possess a series of excellent performances with promising potentials in engineering applications, including high mechanical strength, great fire resistance, enhanced leaching resistance, and improved contaminate stabilization [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%